Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
For Business Enquiry


Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number


Mon to Sat - 11 AM to 8 PM


Asked by 13th February 2009, 10:28 PM
Answered by Expert

The sum of the zeroes of a polynomial  in x =-b/a


 the product of the zeroes=c/a


 a is coefficient of x squared and b is coefficient of the  term in x and c is the term free of x.

So, here,

a=1, b=-8 and c=k

So sum of the zeroes = -b/a= -(-8)/1=8

product of the zeroes=c/a=k

We need to find the sum of squares of the zeroes.

Answered by Expert 14th February 2009, 8:46 AM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp